The Relationship Between Adolescents' Knowledge, Attitudes, And Information Sources Towards Reproductive Health And Sexual Behavior At SMAN 12 Bekasi In 2025 - Indah Yuliani; Inda Panti Nalova (Jurnal Ners, 2026)
Background: Reproductive health is crucial for both men and women. Reproductive health is a state of physical, mental, and social well-being. Knowledge about reproductive and sexual health significantly influences adolescent attitudes. This knowledge is gained through sex education, which provides clear and accurate information about human sexuality. Data collected by the World Health Organization (WHO) in 2023 recorded a prevalence of reproductive organ diseases in women, including bacterial vaginosis, of 23-29%.The main problems in adolescent reproductive health in Indonesia are a lack of information about reproductive health, changes in adolescent sexual behavior, inadequate health services, and inadequate legislation. Currently, the situation of adolescents is increasingly concerning due to the increase in negative actions committed by adolescents. Research Objective: The purpose of this study was to determine the relationship between adolescent knowledge, attitudes, and information sources regarding reproductive health and sexual behavior at SMAN 12 Bekasi in 2025.Research Method: This study used a descriptive analytical approach with a cross-sectional method. Using the Chi-square test, data collection involved independent variables (risk) and dependent variables (risk) at the same time.Research results The results of statistical tests using the Chi Square test showed that respondents with a Level of Knowledge of Reproductive Health with Sexual Behavior obtained a P Value of 0.000 <0.05, for the relationship of Attitude obtained a P Value of 0.001 <0.05, and for the relationship of Information Source obtained a P Value of 0.007 <0.05 there is a significant relationship between knowledge, attitudes and sources of information on Reproductive Health with Sexual Behavior. Conclusions and suggestions As input or reference for further research on the Relationship of Knowledge, Attitudes and Sources of Information of Adolescents on Reproductive Health with Sexual Behavior in areas outside of formal education or non-formal education such as orphanages or street children who have not been exposed to information at all.